On-line estimations of delivered radiation doses in three-dimensional conformal radiotherapy treatments of carcinoma uterine cervix patients in linear accelerator - Suman Kumar Putha (Journal of Medical Physics, 2016)
Transmission of radiation fluence through patient′s body has a correlation to the planned target dose. A method to estimate the delivered dose to target volumes was standardized using a beam level 0.6 cc ionization chamber (IC) positioned at electronic portal imaging device (EPID) plane from the measured transit signal (S t ) in patients with cancer of uterine cervix treated with three-dimensional conformal radiotherapy (3DCRT). The IC with buildup cap was mounted on linear accelerator EPID frame with fixed source to chamber distance of 146.3 cm, using a locally fabricated mount. S t s were obtained for different water phantom thicknesses and radiation field sizes which were then used to generate a calibration table against calculated midplane doses at isocenter (D iso,TPS ), derived from the treatment planning system. A code was developed using MATLAB software which was used to estimate the in vivo dose at isocenter (D iso,Transit ) from the measured S t s. A locally fabricated pelvic phantom validated the estimations of D iso,Transit before implementing this method on actual patients. On-line dose estimations were made (3 times during treatment for each patient) in 24 patients. The D iso,Transit agreement with D iso,TPS in phantom was within 1.7% and the mean percentage deviation with standard deviation is −1.37% ±2.03% (n = 72) observed in patients. Estimated in vivo dose at isocenter with this method provides a good agreement with planned ones which can be implemented as part of quality assurance in pelvic sites treated with simple techniques, for example, 3DCRT where there is a need for documentation of planned dose delivery.